A conceptual comparison between potential configurations in the thermal coupling of naphtha reforming with propane ammoxidation. (March 2020) - Ebrahimian, Samira; Iranshahi, Davood
Abstract: In order to achieve a proper temperature profile and consequently a higher production rate, the conventional catalytic naphtha reforming process (CNR) was coupled thermally with the propane ammoxidation process as a heat source through a novel bifunctional reactor. Propane ammoxidation is a highly exothermic process that occurs on the reactor tube side to supply the required heat for naphtha reforming reactions on the shell side. In this study, the performance of the novel reactor with different types of feeding has been investigated. Two possible counter-current configurations of Series-Naphtha-Parallel-Ammoxidation (SNPA) and Parallel-Naphtha-Parallel-Ammoxidation (PNPA) have been compared with four possible co-current configurations of SNPA, PNPA, Series-Naphtha-Series-Ammoxidation (SNSA), and Parallel-Naphtha-Series-Ammoxidation (PNSA). Among the co-currents, PNPA showed the highest production. The counter series feeding of propane ammoxidation (SNSA and PNSA) was not possible due to the exothermic side's temperature runaway. The results showed that the counter-current SNPA arrangement significantly boosts the heat transfer between the endothermic and the exothermic sides, improving the product yields more than other arrangements and CNR. For counter-current SNPA 42% yield of aromatics was achieved, which is 5% and 7% more than the co-current PNPA and CNR, respectively. In addition, co-current and counter-current configurations were investigated in terms of temperature uniformity. The best configurations in co-current and counter-current were co-SNSA and count-SNPA, respectively. Also, optimization of counter-current SNPA was examined and its results compared with non-optimized results. It was observed that in optimized reactors, the yield of aromatics and the overall yield of acrylonitrile (ACN) were increased to 45% and 41%, respectively.